Evaluation of a concentrated milk replacer and a vitamin-amino acid-iron-electrolyte supplement on baby pig survival and performance - Schoneweis, D.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Litters offered a concentrated milk replacer and the vitamin amino acid, iron-electrolyte supplement, weighed the same as control litters at day 10, 14, 21, and 28. Blood analysis revealed no difference in packed cell volume, hemoglobin, or plasma protein between litters offered the supplement and control litters. Survival rate from birth to weaning favored the control litters (93.9 or 85.3%), however all nineteen litters used in this study were healthy with very little scours observed.
Keywords: Swine; Concentrated milk replacer; Vitamin-amino acid-iron-electrolyte; Survival; Performance